2008
DOI: 10.1111/j.1475-4983.2008.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fossil Record and Evolution of Mousebirds (Aves: Coliiformes)

Abstract: Recent mousebirds are the smallest of the living neognathous bird orders -just two genera comprising six species. Understanding the evolutionary dynamics of this avian lineage is important because these birds occupy a critical position within Neoaves and can be used as a model for patterns of morphological diversification in other taxa. We present a review of all known fossil mousebirds (Aves: Coliiformes), which formed a diverse assemblage in the Paleogene (65-23.8 ma). We also present a new phylogenetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…These stem group Coliiformes were morphologically very diverse and adapted to different locomotory modes and feeding niches. The rather short‐legged species of the Sandcoleidae had a generalized thrush‐like beak and may have been adapted to trunk‐climbing (Houde & Olson , Zelenkov & Dyke ), whereas Chascacocolius was a specialized frugivore with gaping adaptations and a bill‐shape similar to that of some New World blackbirds (Icteridae; Houde & Olson , Mayr ), Celericolius exhibited much longer wings than extant mousebirds, allowing for a more sustained flight in open areas (Ksepka & Clarke ) and the enigmatic Masillacolius had very long legs and presumably fully pamprodactyl feet, with the hindtoe permanently directed forwards (Mayr & Peters ).…”
mentioning
confidence: 99%
“…These stem group Coliiformes were morphologically very diverse and adapted to different locomotory modes and feeding niches. The rather short‐legged species of the Sandcoleidae had a generalized thrush‐like beak and may have been adapted to trunk‐climbing (Houde & Olson , Zelenkov & Dyke ), whereas Chascacocolius was a specialized frugivore with gaping adaptations and a bill‐shape similar to that of some New World blackbirds (Icteridae; Houde & Olson , Mayr ), Celericolius exhibited much longer wings than extant mousebirds, allowing for a more sustained flight in open areas (Ksepka & Clarke ) and the enigmatic Masillacolius had very long legs and presumably fully pamprodactyl feet, with the hindtoe permanently directed forwards (Mayr & Peters ).…”
mentioning
confidence: 99%
“…Previous analyses congruently recovered Selmes as the sister taxon of a clade including all other nonsandcoleid Coliiformes (Ksepka and Clarke, 2010;Mayr, 2013;Mayr and Mourer-Chauviré, 2004;Zelenkov and Dyke, 2008). The analyses of Zelenkov and Dyke (2008) and Ksepka and Clarke (2010) further suggested that Chascacocolius branches next, and that Masillacolius and all other more modern-type Coliiformes form a clade. In the analysis of Mayr (2013), by contrast, the interrelationships of Chascacocolius and Masillacolius were poorly resolved, and Chascacocolius, Masillacolius, and Celericolius were recovered in a polytomy at the base of a clade, which includes all coliiform taxa to the exclusion of sandcoleids and Selmes.…”
Section: Discussionmentioning
confidence: 68%
“…However, their recognition in Oligocolius already raised the question whether these processes may be plesiomorphic for a coliiform subclade, which also includes the crown group representatives (Mayr, 2013). Previous analyses congruently recovered Selmes as the sister taxon of a clade including all other nonsandcoleid Coliiformes (Ksepka and Clarke, 2010;Mayr, 2013;Mayr and Mourer-Chauviré, 2004;Zelenkov and Dyke, 2008). The analyses of Zelenkov and Dyke (2008) and Ksepka and Clarke (2010) further suggested that Chascacocolius branches next, and that Masillacolius and all other more modern-type Coliiformes form a clade.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Phylogenetic Justification. Phylogenetic analysis of morphological data Zelenkov and Dyke, 2008;Clarke, 2009, 2010c). Analyses utilizing a composite Sandcoleidae with scorings from Sandcoleus and several related taxa also support placing Sandcoleus copiosus along the mousebird stem lineage Mayr, 2005d).…”
Section: Coliiformes (Mousebirds)mentioning
confidence: 99%